(untitled) (Research, Society and Development, 2020)
Aim: This experimental study in vitro aimed to compare the disinfection of the primary teeth root canals system using the rotary and reciprocating file system. Methodology: Forty-eight root canals from twenty-four primary molar teeth were contaminated with the standard strain of Enterococcus faecalis and randomically splitted into 4 groups (n=12). The Group PN comprised the root canals prepared with the ProTaperTM Next rotary system. The Group WOG was defined by the usage of WaveOneTM Gold reciprocating system. The files from both systems were thermo mechanical processed. The Group PU used the ProTaperTM Universal system, with no thermic treatment, and the Group C (negative control) received no treatment. Samples from the root canals were collected with sterile paper points before and after its preparation, diluted and distributed in plates with Brain Heart Infusion (BHI) agar. The bacterial colonies were counted and the results were statistic analyzed by Wilcoxon and Kruskal-Wallis (Dunn) tests. Results: There was significant bacterial reduction using the systems (p>0,01). However, there was no significant difference among them (p<0,05) (PN=3.38; WOG=3.85; PU=3.26). Conclusion: Both systems (rotary and reciprocating) provide disinfectionon the primary molar teeth root canals system.